Protective effects of valproic acid against hypoxic-ischemic brain injury in neonatal rats - Kabakus, N; Ay, I; Aysun, S; Söylemezoglu, F; Özcan, A; Celasun, B (B C Decker Inc, 2005)
Although controversial, protective and therapeutic effects of valproic acid in various types of cellular injury suggest a potential role for this agent in hypoxic-ischemic brain injury. We therefore investigated the effects of valproic acid in an experimental model of neonatal hypoxic-ischemic brain injury. To examine the effect of valproic acid in this condition, hypoxic-ischemic brain injury was induced in 7-day-old rat pups by ligation of the right common carotid and then the pups were exposed to I hour of hypoxia in 8% oxygen. Low (200 mg/kg/day) and high (400 mg/kg/day) doses of valproic acid were administered in a 5-day regimen. Neuropathologic evaluation was performed using the hippocampus, cerebral cortex, and basal ganglia in the coronal plane. The 5-day regimen of valproic acid administration resulted in some protective and therapeutic effects on the brain damage and neuronal apoptosis in both hemispheres in a dose-dependent manner. Administration of valproic acid also decreased the percentage of apoptotic neurons in the contralateral hemisphere (P <.05). These results suggest that valproic acid can have therapeutic and protective effects in hypoxic-ischemic brain injury.
Keywords: Cerebral-Artery Occlusion; Different Mechanisms; Encephalopathy; Phenytoin; Damage; Cells; Apoptosis; Glutamate